Efeito da eritorsina na terapia fotodinâmica antimicrobiana em cândida albicans - Rossi, Adriana Leal (2021)
Candida albicans (C. albicans) is a pseudofilamentous dimorphic fungus that can survive and infect humans with difficult resolution by antifungal therapy. Antimicrobial photodynamic therapy (aPDT) generates reactive oxygen species with the potential to kill microorganisms. The erythrosine dye has photodynamic potential and can act on oral microorganisms; therefore, the aim of this work was to investigate the effect of erythrosine-mediated aPDT and blue light on Candida albicans. The cell death time and the incorporation of erythrosine into the fungal cell were evaluated. For the execution of this work, the Candida albicans ATCC 90028 strain was selected, properly prepared for the irradiation test. Irradiation was carried out with a LED dental light-curing device (DMC, São Carlos, SP, Brazil), emitting a wavelength at ʎ = 430 nm – 490 nm and a radiant power of 1000 mW. The samples were irradiated from the top of a 24-well microtiter plate with an irradiance of I = 500 mW / cm2 and radiant exposure of 0 to 377 J/cm2, with irradiation times ranging from 0 to 720 s. The photosensitizer used was Erythrosine at concentrations of 100 μM. Yeast suspensions were divided into groups: Control without irradiation and photosensitizer (L-FS-), irradiated group without photosensitizer (L+720FS-), photosensitizer group without irradiation (L-FS+), and groups that received photosensitizer and irradiation called aPDT groups and described by the acronym L+ followed by the irradiation time in seconds and FS+. To assess the absorption and incorporation of erythrosine, fluorescence microscopy and optical absorption spectroscopy were performed. Erythrosine eradicated the tested microorganisms with total inactivation after 120 s of irradiation and incorporation of photosensitizer into the fungus was observed. APDT mediated by erythrosine and blue light was effective in inactivating Candida albicans.